The reaming of life: based on the 2010 Jim Gray eScience Award Lecture. (17th September 2012) - Bourne, Philip E; Remick, Carolyn; Hunt, James; Javid, Harold; Bougé, Luc; Lengauer, Christian
SUMMARY We are well into the era of data intensive‐digital scientific discovery, an era defined by Jim Gray as the Fourth Paradigm. From my own perspective of the life sciences, much has been accomplished, but there is much to do if we are to maximize our understanding of biological systems given the data we have today, let alone what is coming. In my 2010 Jim Gray eScience Award Lecture, I gave my own thoughts on what needs to be accomplished, and with an additional year of hindsight, I expand on that here. Copyright © 2012 John Wiley & Sons, Ltd.